Single-Cell Sequencing Reveals Types of Hepatopancreatic Cells and Haemocytes in Black Tiger Shrimp (Penaeus monodon) and Their Molecular Responses to Ammonia Stress - Yundong Li; Yundong Li; Yundong Li; Yundong Li; Falin Zhou; Falin Zhou; Qibin Yang; Song Jiang; Jianhua Huang; Lishi Yang; Zhenhua Ma; Shigui Jiang; et al. (Frontiers in Immunology, 2022)
The cell types and developmental trajectories of shrimp cells based on the transcriptional level have not been established, and gene expression profile and function at the single-cell level is unclear. We aimed to use scRNA-seq to construct a single-cell resolution transcriptional map of hepatopancreas and haemocytes in shrimp to analyse the molecular mechanisms of the immune response to ammonia nitrogen stress. In the present study, seven cell clusters were successfully identified in each of the two tissues (haemocytes, Hem1-7; hepatopancreas, Hep1-7) based on specifically-expressed marker genes. The developmental starting points of haemocytes and hepatopancreatic cells were Hem2 and Hep1, respectively. We propose that Hem2 has oligopotent potential as the initiation site for haemocyte development and that Hem4 and Hem5, located at the end of development, are the most mature immune cell types in haemocytes. Hep5 and Hep6 were the developing terminal cells of hepatopancreas. The antioxidant system and proPO system of shrimp were activated under ammonia nitrogen stress. A large number of DEGs were involved in oxidative stress, detoxification metabolism, and immune defence. In particular, important response genes such as AMPs, proPO, and GST were not only marker genes for identifying cell groups but also played an important role in shrimp cell differentiation and functional plasticity. By successfully applying 10× Genomics based scRNA-seq to the study of shrimp, the single-cell transcriptional profiles of hepatopancreatic cells and haemocytes of shrimp innate immune responses under ammonia stress were constructed for the first time. This atlas of invertebrate hepatopancreatic cells and haemocytes at single-cell resolution identifies molecular events that underpin shrimp innate immune system responses to stress.